1993
DOI: 10.1111/j.1475-097x.1993.tb00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic detection of gastro‐pulmonary aspiration in patients with respiratory disorders

Abstract: The scintigraphic detection of small nocturnal aspirations of radio-labelled gastric contents is difficult in the presence of high remaining activity in the abdomen, causing a non-uniform background activity. This problem was examined in phantom experiments and a technique for interpolative background correction was further developed. The accuracy of this technique was found to be influenced by the distance between the lung and the abdominal source of activity, and the minimum detectable 'aspirated' activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 19 publications
0
22
0
4
Order By: Relevance
“…The specificity of the latter is reported to be as low as 57% [4], whereas contrast studies and scintigraphy have low sensitivity [5]. Prolonged intraesophageal pH monitoring is widely regarded as the gold standard for diagnosing GER.…”
mentioning
confidence: 99%
“…The specificity of the latter is reported to be as low as 57% [4], whereas contrast studies and scintigraphy have low sensitivity [5]. Prolonged intraesophageal pH monitoring is widely regarded as the gold standard for diagnosing GER.…”
mentioning
confidence: 99%
“…[3][4][5][6] A causative relation is still unclear, even though acid perfusion of the lower oesophagus may induce bronchoconstriction in animal models 7 and in humans, 8 9 probably mediated through a vagal reflex. 9 Microaspiration is an alternative pathophysiological mechanism, as shown by scintigraphic studies 10 and analyses of bronchoalveolar lavage fluid. 11 12 A limited number of studies reviewed in a recent Cochrane report 13 have evaluated the effect of GORD treatment, with conflicting results with respect to asthma symptoms and lung function.…”
mentioning
confidence: 99%
“…Ruth M et al in their study have shown that pulmonary scintigraphy is low sensitivity and has a diagnostic yield below 20%, but a positive test result is of great diagnostic value. 10 The male to female ration in our study was 1.6:1 and three was no significant correlation between sex and efflux x 2 =0.…”
Section: Discussionmentioning
confidence: 89%